POTENSI EKONOMI HIJAU DI DESA SURANADI KECAMATAN NARMADA KABUPATEN LOMBOK BARAT DALAM MENGEMBANGKAN PRODUK TANAMAN PANGAN PADI BERAS MERAH - Wahab, Alvionita Safira; Adiningtyas, Baiq Faras Sukma; Astuti, Femi Dwi; Adiguna, I Gede Divbodhi; Maharani, Kadek Dyah Aurelia; Salahuddin, Muamar Omar; Salwa, Nabila Widhi; Husain, Nadia Salsabila; Arghyanita, Ni Luh Made Swasti; Suharijanto, Richardo Amos (Universitas Mataram, 2024)
This community service activity aims to introduce the Impago Unram 1 variety (red rice) to farmers in Suranadi village in a sustainable manner through counseling and direct cultivation practices to farmers, especially the Mata Air 1 and 2 farmer groups located in the North Suranadi area. The results of this counseling show that farmers are enthusiastic about the dissemination of this new variety. Likewise, the village government institutions feel very helped by the direct practice of cultivating red rice. The positive impact of this activity is that farmers' knowledge of food diversity or diversification is increasing, which will be in line with the welfare of the economic aspects in the community, especially food crop farmers. It is hoped that there will be continuous assistance so that food independence can be realized and then the Impago Unram 1 rice variety can become a superior commodity in Suranadi Village.